Pengembangan E-Book Interaktif DARBUKA Bermuatan Alat Musik Madura untuk Siswa Kelas V SDN Telang 1 - Rika Nur Hamida; Fachrur Rozie (Jurnal Pendidikan, Sains, Geologi, dan Geofisika (GeoScienceEd Journal), 2026)
Learning in the Merdeka Curriculum encourages the use of digital and contextual teaching materials that actively engage students. However, science learning on sound for fifth-grade students at SDN Telang 1 still relied on printed textbooks and teacher-centered instruction, making it difficult for students to understand abstract concepts while local cultural content was rarely integrated into learning. This study aims to develop the DARBUKA Interactive E-book incorporating Madurese musical instruments for fifth-grade students of SDN Telang 1 that is valid, effective, and attractive. This research employed the Research and Development (R&D) method using the 4D model, consisting of the Define, Design, Development, and Disseminate stages. The results showed that the DARBUKA Interactive E-book achieved a very high level of validity, with learning design validation of 95%, material validation of 91.67%, and teaching material validation of 83.75%. In terms of effectiveness, the e-book achieved 100% student learning mastery in both the limited trial and implementation stages, supported by teacher and student activities categorized as very good. Teacher responses reached 97.5% (very attractive), while student responses were categorized as attractive. Therefore, the DARBUKA Interactive E-book is feasible as a teaching material because it is valid, effective, and attractive, while supporting active, interactive, meaningful, and culturally contextual learning for elementary school students.